Bitte Recht verständlich! Evaluation der Gesetzesredaktion des Bundes bei der Verständlichkeitsoptimierung von Rechtsvorschriften - Vogel, Friedemann; Schmallenbach, Joline (ZERL - Zeitschrift für Europäische Rechtslinguistik, 2021)
This article reports on a completed research project on the evaluation of the linguistic legal editorial in the German Federal Ministry of Justice and Consumer Protection (2019-2021). The study focuses on the development of a holistic model of criteria for assessing the comprehensibility of norm texts, an empirical typing of comprehensibility criteria, and the survey of reception patterns of norm texts edited by law-editors. The study confirms that intensive cooperation between legal linguists and legal experts is necessary to make laws more comprehensible and legal practice more efficient.